2001
DOI: 10.1046/j.1471-4159.2001.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative impairment in scrapie‐infected mice is associated with brain metals perturbations and altered antioxidant activities

Abstract: Prion diseases are characterized by the conversion of the normal cellular prion protein (PrP C ) into a pathogenic isoform (PrP Sc ). PrP C binds copper, has superoxide dismutase (SOD)-like activity in vitro, and its expression aids in the cellular response to oxidative stress. However, the interplay between PrPs (PrP C , PrP Sc and possibly other abnormal species), copper, anti-oxidation activity and pathogenesis of prion diseases remain unclear. In this study, we reported dramatic depression of SOD-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 41 publications
4
84
1
1
Order By: Relevance
“…Watt et al (2005) suggested that the Cu-bound octarepeat-dependent progress in β-cleavage of PrP C is an early and critical event in the mechanism of protecting cells by PrP acting against the oxidative stress. Furthermore, it was shown that Cu-bound PrP C possesses some superoxide dismutase (SOD)-like activity in vitro, and its expression likely contributes to the cellular response to oxidative damages to cells (Wong et al, 2001). Sauer et al (1999) have proposed that PrP C expression in tumour spheroids is regulated by the internal redox statuses meeting the requirement to protect cells from ROS since they have observed in tumour spheroids that an increase in ROS stimulates the production of PrP C and other ROS-scavenging enzymes such as Cu,Zn-SOD and catalase, while ROS-lowering treatments effectively down-regulate the expression of both ROS-scavenging enzymes and PrP C .…”
Section: Mechanism Of Peptide Actionmentioning
confidence: 99%
“…Watt et al (2005) suggested that the Cu-bound octarepeat-dependent progress in β-cleavage of PrP C is an early and critical event in the mechanism of protecting cells by PrP acting against the oxidative stress. Furthermore, it was shown that Cu-bound PrP C possesses some superoxide dismutase (SOD)-like activity in vitro, and its expression likely contributes to the cellular response to oxidative damages to cells (Wong et al, 2001). Sauer et al (1999) have proposed that PrP C expression in tumour spheroids is regulated by the internal redox statuses meeting the requirement to protect cells from ROS since they have observed in tumour spheroids that an increase in ROS stimulates the production of PrP C and other ROS-scavenging enzymes such as Cu,Zn-SOD and catalase, while ROS-lowering treatments effectively down-regulate the expression of both ROS-scavenging enzymes and PrP C .…”
Section: Mechanism Of Peptide Actionmentioning
confidence: 99%
“…Key involvement of metals (especially copper) in prion diseases has been well documented by a number of works (Watt et al, 2005;Wong et al, 2001;Sauer et al, 1999). However, two opposing roles for copper-bound PrPs have been proposed, namely as anti-oxidants and contrary as pro-oxidants enhancing the neurodegenerative process (Opazo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, two opposing roles for copper-bound PrPs have been proposed, namely as anti-oxidants and contrary as pro-oxidants enhancing the neurodegenerative process (Opazo et al, 2003). The likely factors associated with generation (Kawano, 2007) or removal of ROS (Wong et al, 2001) within PrPs are Cu-binding sequences highly preserved in PrPs.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism leading to the development of protein aggregates and accompanying neurotoxicity is relatively clear for some of these conditions, whereas in others, it is still debated. Recent evidence suggests the imbalance of brain metal homeostasis as a common cause of neuronal death in several of these disorders (9,45,48,60,61,70,111,148,171,203,242). It is believed that a redox-active metal interacts with a specific protein and is reduced in its presence, resulting in the generation of reactive oxygen species (ROS), hydrogen peroxide (H 2 O 2 ), and hydroxyl radicals (OH ) that cause aggregation of the involved protein (16,206,215,224,225).…”
mentioning
confidence: 99%